Baby, it's cold outside: Climate model simulations of the effects of the asteroid impact at the end of the Cretaceous. Issue 1 (13th January 2017) - Brugger, Julia; Feulner, Georg; Petri, Stefan
Abstract: Sixty‐six million years ago, the end‐Cretaceous mass extinction ended the reign of the dinosaurs. Flood basalt eruptions and an asteroid impact are widely discussed causes, yet their contributions remain debated. Modeling the environmental changes after the Chicxulub impact can shed light on this question. Existing studies, however, focused on the effect of dust or used one‐dimensional, noncoupled atmosphere models. Here we explore the longer‐lasting cooling due to sulfate aerosols using a coupled climate model. Depending on aerosol stratospheric residence time, global annual mean surface air temperature decreased by at least 26°C, with 3 to 16 years subfreezing temperatures and a recovery time larger than 30 years. The surface cooling triggered vigorous ocean mixing which could have resulted in a plankton bloom due to upwelling of nutrients. These dramatic environmental changes suggest a pivotal role of the impact in the end‐Cretaceous extinction. Key Points: We use a coupled climate model to investigate the effects of sulfate aerosols and carbon dioxide from the Chicxulub impact We find severe cooling suggesting a major role of the impact in the mass extinction event Surface cooling of the ocean results in vigorous mixing which could have caused a plankton bloom